INCREASING LANGUAGE LITERACY OF UNIVERSITY STUDENTS - Turaeva Shahida Egamberdievna (Western European Studies, 2024)
Currently, high demands are placed on the level of linguistic literacy of university students. But not all first-year students meet the demands put forward by higher education: language skills and speech skills are not sufficiently developed, which is a serious omission of general education institutions. The article presents a fragment of an experimental study in which a communicative-activity approach was introduced, aimed at increasing the language literacy of students. Experimental learning includes three stages: the ascertaining stage, at which the literacy level of the students participating in the experiment was diagnosed, the teaching stage, aimed at developing the appropriate skills, and the control or analytical stage, which is the result of the experimental learning
Keywords: Language literacy; language resources; society; linguistic personality